ANALISIS PRODUKSI USAHATANI JAGUNG DI DESA OLOBOJU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - M. Fardhal Pratama (Universitas Tadulako, 2016)
The aims of the research were: (1) to determine the effect of land area size, seeds, urea and KCl fertilizer, pesticides, and labors on the production of corn in Oloboju village Sigi Biromaru sub district of Sigi district, and (2) to determine the income of the corn farming system in Oloboju village Sigi Biromaru sub district of Sigi district. Farmer respondents of 32 people were purposively selected. The results of analysis showed that simultaneously such factors as seeds (X2), fertilizers (X3), and pesticides (X4) had significant effect on the corn production whereas land area size (X1) and labor (X5) are not significant. The Fcounted was 10.557>the Ftable (3.297) at 90% level, thus H0 was rejected and H1 accepted. The results of analysis indicated that the average income of the corn farmers in Oloboju village Sigi Biromaru sub district of Sigi district was IDR 1,240,526/0.46 ha. Key Words: Corn Farming, Fram Income and Production.